In-situ growth of highly monodisperse ITO nanoparticles regulated by mesoporous silica glasses. (5th August 2018) - Chen, Ping; Chen, Zhangru; Hou, Shaodong; Shen, Xiang; Chu, Yingbo; Yang, Yu; Yang, Luyun; Li, Jinyan; Dai, Nengli
Abstract: In this work, we firstly introduce a facile method to synthesize bulk silica glass contained indium tin oxide nanoparticles (ITO NPs). Water solution with InCl3 and SnCl4 was mixed and dipped into the mesoporous silica glass (MSG) followed by an in-situ growth of ITO NPs under 1000 °C heat treatment. X-ray diffraction (XRD) and transmission electron microscopy (TEM) show that the ITO NPs are highly monodisperse and crystalline in the silica glass with size around 20–30 nm. The size and distribution of ITO NPs can be regulated by the mesopores of mesoporous silica glass (MSG) effectively. The absorption and photoluminescence (PL) spectra exhibit an optical band gap and a PL emission of the ITO NPs doped silica glass at 3.12 eV and 560 nm, respectively. Results indicate that this kind of composite material has potential applications for optical nonlinearity, plasmonic formation, and sensing in the future. Graphical abstract: Unlabelled Image Highlights: Monodisperse and crystalline indium tin oxide nanoparticles (20-30 nm) are synthesized in silica glasses through an in-situ formation firstly. The nanopores (mainly 15-30 nm) in mesoporous silica glasses are used to tailor the distributions of ITO NPs effectively. Defects (arising from the Sn 4+ substitution and oxygen vacancies) related photoluminescence centred at 560 nm of the ITO NPs doped silica glass was observed and discussed.